KAIDAH FIKIH LȂ MASȂGA LI AL IJTIHȂD FȊ MAURID AL NAS: HAKIKAT TEORI IJTIHAD DAN APLIKASINYA - Andi Muhammad Akmal (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
The use of Jurisprudence in the stage of ijtihad is needed to answer the problem of public awareness, along with the development of science and technology. This study aims to analyze the urgency and nature of the principles of fiqh in islamic law and find out the signs and limits of the scope of one’s ability to ijtihad against new legal issues and explore the application of fiqh principles of lā masāga li al-ijtihād fi maurid al-nas in social reality. This study is descriptive qualitative with a sociological normative juridical approach. The results of the study show that the urgency and existence of fiqh principles in sresponding to the problem of community diversity is very significant. That ulama, fuqaha an law practitioners, must do ijtihad in an effort to find a new law. The effort must be based on the understanding that ijtihad on certain problems can only be done if there s no found nas} qat}’i for a problem or whether there is a passage but it is zanni. Orders to carry out obligations and stay away from restrictions in the activities of Muslims as an inseparable part of the applicaton of these rules